Econometric analysis for tourism sector in ASEAN - Chanamart Intapan (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Tourism remains important to the worldwide economy. For Thailand, the worth of Tourism Direct GDP (TDGDP) is 5.45% compared to the country's total GDP. Moreover, MICE or business event travel industry generated 10.7% of the sector's annual income, with the typical industry growth of 15‐20%. Therefore, to maintain the competitiveness of Thai tourism, studying and understanding Thai tourism behavior is vital. However, there are still only a few studies on business tourism and therefore the efficiency of Thai tourism. This study focused on business tourism and also the efficiency of tourism. This thesis consists of three articles. The primary article is an analysis of the impact of tourism demand on gross domestic product. The second article examines the long-term equilibrium of the connection between MICE to the Thai economy. The third article examines the efficiency of Thai tourism. Studying the impact of tourism demand on the economy is extremely important for policymakers in making policy decisions. The most important question of this study is whether or not tourism demand and gross domestic product are seasonal. Therefore, this study is to research the seasonal fluctuations of tourism demand on gross domestic product. Therefore, we select the model that has seasonal pattern into consideration. The chosen model was the Bayesian seasonal unit root test. The study found that time series data is non-stationary. From the study, we will conclude that policymakers should consider the seasonal as the variable in tourism strategy. Since the results of the study have shown that tourism demand, namely the amount of tourists, tourism revenues, and tourism expenditures are all variables that are the seasonal unit root for the long-term. The second article analyzes the long-term equilibrium of the connection between MICE to the Thai economy by using the ADF unit root test and ARDL approach to cointegration with the concepts of recent econometrics called the Bayesian approach. The study found that both MICE tourists and MICE revenues have a short-term and long-term relationship with Thailand's gross domestic product. This study shows that business tourist groups are attractive target groups. Governments and therefore the private sector should pay more attention to the present group of tourists to stimulate the country's economy. The final study examines the efficiency of the tourism sector in Thailand compared to Malaysia and Singapore by measuring the efficiency of the frontier approach. The chosen models are the bootstrap DEA and the Stochastic Frontier Analysis model. The results from the bootstrap DEA model showed that the best tourism performance score was Singapore, followed by Malaysia and Thailand respectively. The results from the Stochastic Frontier Analysis model found that the best tourism performance score was Malaysia, followed by Singapore and Thailand respectively. This study indicates that although Thailand has more tourists than Singapore and Malaysia, the Thai tourism sector remains not efficient. We will conclude that Thailand's tourism sector in comparison to other ASEAN countries, remains ready to increase efficiency.